Spatial Arrangement of Coastal Settlements from the Perspective of Slum Conditions: A Systematic Review - Ismail, Indah Virda Auliyanti; Wikantiyoso, Respati; Wahjutami, Erlina Laksmiani; Utaberta, Nangkula (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study is a systematic review focusing on the spatial arrangement of coastal settlements viewed from the perspective of slum conditions. It aims to analyze and synthesize previous research findings that discuss spatial dynamics, environmental challenges, and adaptive management strategies in coastal residential areas experiencing settlement degradation or slum formation. A total of 32 national and international journal articles were reviewed, selected from approximately 100 initial publications based on thematic relevance and methodological quality. The literature review process was conducted using the Google Scholar and SciSpace databases with the keyword “Coastal Settlements of the Slums.” Each article was analyzed and categorized into five main thematic clusters: (1) spatial morphology and transformation, (2) environmental and climatic impacts, (3) physical and social characteristics of settlements, (4) management and adaptation strategies, and (5) governance and housing policy. The synthesis reveals that improving the spatial quality and resilience of coastal slum settlements requires more than physical interventions; it demands an evidence-based integrative approach that combines spatial planning, community empowerment, institutional collaboration, and adaptive, participatory governance. Therefore, this review strengthens the conceptual understanding of spatial–social relationships in coastal environments and emphasizes the importance of interdisciplinary approaches in achieving resilient, inclusive, and sustainable coastal settlements.